Pronunciation and Aeronautical English: Brazilians’ difficulties and possible routes to intelligibility - Babboni, Carlos Alberto; Quast, Karin (The ESPecialist, 2020)
Communications between pilot and air traffic controller (ATCO) are carried out via radiotelephony, without visual contact between the interlocutors. ICAO, a specialized agency of the United Nations, is responsible for the security of international civil aviation. ICAO’s official documents (ICAO, 2004, 2009, 2010) mention the importance of English pronunciation in the intelligibility of pilot-ATCO communication. In 2017, Brazilian researchers analyzed the extent to which two international Aeronautical English (AE) textbooks, used in an ATCO training course in Brazil, address the pronunciation difficulties considered typical among Brazilians (CRISTÓFARO-SILVA, 2012). The analysis, based on the concepts of intelligibility, English as a Lingua Franca and the ‘Lingua Franca Core’ (JENKINS, 2000, 2002, 2005), showed that the analyzed books do not portray several of these difficulties. In this article, we first point out international air accidents and incidents in which pronunciation was one of the contributing factors, then, based on the Lingua Franca Core, we discuss the causes of some Brazilian pronunciation difficulties, aiming to increase teachers’ and students’ awareness and to contribute to pronunciation teaching in the field of AE. In addition, we problematize the non-critical use of textbooks by teachers and the inadequate training in English Language Phonology.